6=-3(d-9)

Simple and best practice solution for 6=-3(d-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=-3(d-9) equation:


Simplifying
6 = -3(d + -9)

Reorder the terms:
6 = -3(-9 + d)
6 = (-9 * -3 + d * -3)
6 = (27 + -3d)

Solving
6 = 27 + -3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '3d' to each side of the equation.
6 + 3d = 27 + -3d + 3d

Combine like terms: -3d + 3d = 0
6 + 3d = 27 + 0
6 + 3d = 27

Add '-6' to each side of the equation.
6 + -6 + 3d = 27 + -6

Combine like terms: 6 + -6 = 0
0 + 3d = 27 + -6
3d = 27 + -6

Combine like terms: 27 + -6 = 21
3d = 21

Divide each side by '3'.
d = 7

Simplifying
d = 7

See similar equations:

| 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 | | -6n+3=-9 | | 2x-44=4x-88 | | 4n+10=2n-5 | | N-6=21-8n | | 9x+10y=500 | | (n-6)+6=12 | | (m-1)x^2-(m-1)x+m+5=0 | | 3(f+1)=6 | | X^3=2x-38 |

Equations solver categories